Correlation dependences of petrophysical parameters of rocks of the Ukrainian Shield under different pressures and temperatures - Karnaukhova, O.Ye. (Geofizicheskiy Zhurnal, 2025)
Using an extended data bank of the Ukrainian Shield, a search for correlations between petrophysical parameters of rocks was conducted. The differentiation of selected groups of rocks of different mineral composition by the propagation velocities of elastic waves and density at different pressures and temperatures has been confirmed. Unambiguous, mainly directly proportional dependencies have been established between elastic, elastic and electrical parameters with high enough pair-wise correlation coefficients.